Intrauterine versus external tocodynamometry in monitoring labour: a randomised controlled clinical trial. (16th July 2020) - Hautakangas, T; Uotila, J; Huhtala, H; Palomäki, O
Abstract : Objective: To investigate whether the use of intrauterine tocodynamometry versus external tocodynamometry (IT versus ET) during labour reduces operative deliveries and improves newborn outcome. As IT provides more accurate information on labour contractions, the hypothesis was that it may more appropriately guide oxytocin use than ET. Design: Randomised controlled trial. Setting: Two labour wards, in a university tertiary hospital and a central hospital. Population: A total of 1504 parturients with singleton pregnancies, gestational age ≥37 weeks and fetus in cephalic position: 269 women with uterine scars, 889 nulliparas and 346 parous women with oxytocin augmentation. Methods: Participants underwent IT ( n  = 736) or ET ( n  = 768) during the active first stage of labour. Main outcome measures: Primary outcome: rate of operative deliveries. Secondary outcomes: duration of labour, amount of oxytocin given, adverse neonatal outcomes. Results: Operative delivery rates were 26.9% (IT) and 25.9% (ET) (odds ratio 1.05, 95% CI 0.84–1.32, P  = 0.663). The ET to IT conversion rate was 31%. We found no differences in secondary outcomes (IT versus ET). IT reduced oxytocin use during labours with signs of fetal distress, and trial of labour after caesarean section. Conclusions: IT did not reduce the rate of operative deliveries, use of oxytocin, or adverse neonatal outcomes, and it did not shorten labour duration. Tweetable abstract: IT (versus ET) reduced oxytocin use in high‐risk labours but did not influence operative delivery rate or adverse neonatal outcomes. Tweetable abstract: IT (versus ET) reduced oxytocin use in high‐risk labours but did not influence operative delivery rate or adverse neonatal outcomes.